Fiqh Muâ€™Ämalah in Theory and Practice: An Overview of Islamic Economics - Al Hadi, M Qoshid (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The Islamic economic paradigm and worldview have resulted in competitive Islamic finance industry in global finance. In the face of intense competition in the global financial industry, Islamic finance requires innovative contracts or products based on sharia through fiqh muâ€™Ämalah. This article aims to understand the issue of fiqh muâ€™Ämalah in Islamic economics. Using descriptive analysis, the author describes the relationship between fiqh muâ€™Ämalah and sharia finance and the prohibition of muâ€™Ämalah, hybrid-contract, MaqÄshid sharia, and its supervision. The conclusion in this article clarifies the concept of the prohibition of fiqh muâ€™Ämalah to its supervision without hindering the innovation of Islamic financial activities.Paradigma ekonomi Islam dan cara pandangnya (worldview) telah menghasilkan industri keuangan syariah yang kompetitif dalam keuangan global. Dalam menghadapi persaingan sengit industri keuangan global maka keuangan syariah membutuhkan akad atau produk yang inovatif berbasis syariah melalui fiqih muâ€™Ämalah. Artikel ini bertujuan untuk memahami isu fiqih muâ€™Ämalah dalam studi ekonomi Islam. Dengan menggunakan analisis deskriptif, penulis mendeskripsikan hubungan fiqih muâ€™Ämalah dan keaungan syariah serta larangan muâ€™Ämalah, multi akad, MaqÄshid syariah dan pengawasannya. Kesimpulan dalam artikel ini menjernihkan konsep tentang larangan fiqih muâ€™Ämalah hingga pengawasannya tanpa menghambat inovasi dari aktivitas keuangan syariah.